Dynamic changes of intestinal flora in patients with irritable bowel syndrome combined with anxiety and depression after oral administration of enterobacteria capsules. Issue 2 (20th December 2021) - Guo, Qingqing; Lin, Hao; Chen, Pengcheng; Tan, Songlin; Wen, Zhiyong; Lin, Lijian; He, Jianquan; Wen, Jianbo; Lu, Shiyun
ABSTRACT: This study investigated the clinical characteristics and dynamic changes of intestinal bacterial community to evaluate the curative effect of fecal microbiota transplantation (FMT) on irritable bowel syndrome with predominant diarrhea (IBS-D) comorbid with anxiety and depression. Total two treatments were designed in randomize-controlled trial includes oral FMT capsules with 1 week (A1), 8 weeks (A2), and 12 weeks (A3), as well as oral empty capsules with 1 week (B1), 8 weeks (B2), and 12 weeks (B3) as control for comparison. The positive therapeutic effects occurred in FMT colonized patient with IBS-D comorbid psychological disorder, demonstrated at alleviated IBS-D severity (IBS-SSS score from 291.11 reduced to 144.44), altered stool type (from 6 changed to 4), reduced anxiety and depression scores (from 18.33 to 8.39 and from 22.33 to 17.78) after FMT-treated 12 weeks. The FMT therapy improved bacterial alpha diversity and the majority bacterial community predominant by Bacteroidetes and Firmicutes, and the relative abundance (RA) was higher after FMT-treated 12 weeks (50.61% and 45.52%) than control (47.62% and 38.96%). In short, FMT therapy has great potential for IBS-D patients combined with anxiety and depression by alleviated clinical symptoms and restore the intestinal micro-ecology. Graphical abstract: uf0001